2016
DOI: 10.1093/mnrasl/slw076
|View full text |Cite
|
Sign up to set email alerts
|

No sign (yet) of intergalactic globular clusters in the Local Group

Abstract: We present Gemini/GMOS imaging of twelve candidate intergalactic globular clusters (IGCs) in the Local Group, identified in a recent survey of the SDSS footprint by di Tullio Zinn & Zinn (2015). Our image quality is sufficiently high, at ∼ 0.4 ′′ − 0.7 ′′ , that we are able to unambiguously classify all twelve targets as distant galaxies. To reinforce this conclusion we use GMOS images of globular clusters in the M31 halo, taken under very similar conditions, to show that any genuine clusters in the putative I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…The value of 4.7 for a fiducial 10 12 M MW halo would correspondingly suggest that for 30% of the sky (i.e. the SDSS result from di Tullio Zinn & Zinn 2015 and Mackey et al 2016) the expected value would be 1.4 IGCs and, assuming Poisson statistics, that the probability of observing zero is exp(−1.4) ≈ 25%, and easy to accommodate (by extension also true for the higher redshift cut). In the future, as more GCs are identified in the outskirts of our galaxy, the observation of isolated GCs free floating between galaxies might become an exciting constraint to the models.…”
Section: The Abundance Of Intergalactic Globular Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of 4.7 for a fiducial 10 12 M MW halo would correspondingly suggest that for 30% of the sky (i.e. the SDSS result from di Tullio Zinn & Zinn 2015 and Mackey et al 2016) the expected value would be 1.4 IGCs and, assuming Poisson statistics, that the probability of observing zero is exp(−1.4) ≈ 25%, and easy to accommodate (by extension also true for the higher redshift cut). In the future, as more GCs are identified in the outskirts of our galaxy, the observation of isolated GCs free floating between galaxies might become an exciting constraint to the models.…”
Section: The Abundance Of Intergalactic Globular Clustersmentioning
confidence: 99%
“…outside the virial radius of galaxies and clusters. Whereas promising new measurements from observations are starting to constrain the kinematics of GCs (Zhu et al 2014;Deason et al 2013;Napolitano et al 2014;Spitler et al 2012), the searches for 'intergalactic' GCs in the large SDSS data-set has not confirmed any candidates so far (di Tullio Zinn & Zinn 2015;Mackey et al 2016). Therefore, as observational data starts to constrain the full space of predictions by the model, the jury is still out on whether primordial GCs could explain (or partially explain) the population of metal poor GCs around galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, measuring the redshift evolution of the rates will represent an observation probe of GC formation, their initial numbers in the Universe and their evolution across cosmic time. With a sufficiently large sample of mergers the relative contribution of intergalactic GCs [54,55] may be distinguished from GCs evolving in galaxies. Future instruments such as the Voyager, Einstein Telescope, or Cosmic Explorer will make this endeavor more feasible [52,56].…”
mentioning
confidence: 99%
“…Based on estimated distances to several GCs found in the Palomar Observatory Sky Survey, van den Bergh (1958) reported the discovery of several intergalactic GCs (the equivalent of ICGCs outside of clusters) in the Local Group. However, these objects are now generally considered distant members of the Galactic GC system, and the existence of truly intergalactic GCs in the Local Group remains in dispute (Mackey et al 2016). West et al (1995) proposed large numbers of ICGCs could be responsible for the high values of S N found for many brightest cluster galaxies (BCGs); these high-S N BCGs would have additional GCs associated to them because of their privileged positions within cluster centers.…”
mentioning
confidence: 99%